Improving the Performance of Pkh Social Assistance Assessed by The Perspective of Social Intelligence Based on Catur Paramitha And Work Commitments - Dewi, Komang Trisna Sari; Romayanti, Komang Nyanyi (International Journal of Social Science and Business, 2020)
The Family of Hope Program (PKH) is one of the flagship programs of the Indonesian Ministry of Social Affairs in an effort to alleviate poverty. This study aims to analyze the role of social intelligence based on Catur Paramitha and work commitment to the performance of PKH Social Assistants in an effort to alleviate poverty. The number of samples in this study were 64 respondents who were selected using the nonprobability sampling method. The sampling technique in this study was purposive sampling. The data analysis techniques used in this study were variance-based and component-based SEM structural equation models with smart PLS 3.0 analysis tools. Based on the results of hypothesis testing, it shows that Catur Paramitha-based Social Intelligence has a positive and significant relationship to the Performance of the Companion. Second, Catur Paramitha based Social Intelligence has a positive and significant relationship to Work Commitment. Third, Work Commitment has a positive and significant relationship to the Companion's Performance.